Analisis Implementasi Kebijakan Sistem Ganjil Genap Dalam Mengatasi Kemacetan Di Provinsi DKI Jakarta - Ahmad Hidayat Rahadian; Munir Saputra; Delfina Ramadhanty (Jurnal Reformasi Administrasi : Jurnal Ilmiah untuk Mewujudkan Masyarakat Madani, 2022)
Road congestion is a major problem for the City of Jakarta due to the high volume of private vehicles on the road, especially along office roads such as Jalan MH Thamrin, Gatot Subroto and Sudirman area, so that the DKI Jakarta Provincial Government, through the Jakarta Transportation and Transportation Agency, issued a public policy that limits the use of private vehicles with an odd-even system. This study aims to determine the impact of implementing this policy in reducing congestion. The research was conducted using qualitative methods through in-depth interviews with several key informants. The results show that the implementation of this policy has gone well, distances on protocol roads have become shorter, congestion has decreased, and the use of public transportation has begun to increase. However, in its implementation, there are still some obstacles, such as violations by the community and some residents who have more than two private vehicles with different police numbers, so that the results of this implementation are less than optimal. The negative impact of this policy is the discovery of people who falsify their vehicle registration number. Meanwhile, the positive impact is that in the long term this policy will increase the shift of people to use public transportation.